High radix booth multipliers using reduced area adder trees - Gallagher, W.L.; Swartzlander, E.E. (Proceedings of 1994 28th Asilomar Conference on Signals, Systems and Computers, 1994)
The reduced area multiplier, the Wallace multiplier, and the Dadda (1965) multiplier each offer fast multiplication of signed binary numbers with the use of a large adder tree and a carry lookahead adder. However, their complexity makes them undesirable for some applications. A Booth (1951) multiplier, on the other hand, offers simplicity and flexibility, by both breaking a multiplication up into pieces, and by allowing the size of the pieces to be chosen. Unfortunately, Booth multipliers become difficult to design for higher radices. The use of a fast adder tree, such as that found in a reduced area multiplier, permits straightforward design of very high radix Booth multipliers. Increasing the radix of a Booth multiplier in this manner results in large increases in speed with reasonable hardware cost.< >